Prospects for Increasing Production and Supply Chain of Cayenne Pepper in Indonesia - Jeksen, Elfius Elwi; Asnah, Asnah; Dyanasari, Dyanasari (Agro Bali : Agricultural Journal, 2024)
Chili is a horticultural commodity that has made significant contributions and has significant economic value in Indonesia. The prospect of increasing cayenne pepper production in Indonesia using simple linear regression analysis with chili production data from 1990-2022 has increased quite significantly. The attributes and results are added together to obtain the supply chain performance value based on performance attributes. These values are classified into standard performance values. The supply chain performance value based on attributes is 93.26 out of 100%. This value is obtained by adding up the values of each performance attribute. This value indicates that the performance of the Cayenne pepper supply chain in Indonesia is in the Good criteria (Above Average) based on the classification of standard work values. The SPSS output has an adjusted determination coefficient (Adjusted R Square) of 0.393. This means that 39.3% of the dependent variable (production (Y) is influenced by exports (X1) and imports (X2), while the remaining 60.7% (100% - 39.3) is influenced by other variables outside the variables used.